Analysis Of E-Pnbp Application System Development For Pnbp Optimization Of Mineral And Coal Sub-Sector - Muhammad Syahirul Alim; Yoke Pribadi Kornarius (Jurnal Indonesia Sosial Teknologi, 2023)
Non-tax revenue (PNBP) is a collection other than taxes paid by individuals, groups or business entities as an obligation to the state for the utilization of natural resources. Increasing the optimization of non-tax revenues is still a challenge for the Directorate General of Mineral and Coal in managing PNBP. The existence of the e-PNBP application aims to make monitoring of PNBP obligations much easier to carry out. This application was created to facilitate the calculation of PNBP obligations by the payer, facilitate evaluation and verification of PNBP obligations by evaluators, and as a function of payment of mineral and coal PNBP obligations so that they are in accordance with the calculated value of PNBP obligations. At present, the e-PNBP application is one of the most dynamic among others in terms of facilitating various changes and adjustments to regulations related to mineral and coal mining. In its development, the e-PNBP application requires integration with other applications such as MODI, SIMPONI, MOMS, MVP and SERASI, as well as various other developments.